FWHM Dimentional Analysis from Scattered Light Intensity Profile for Dry Rubber Content Determination in Natural Rubber - Ikha Rasti Julia Sari; Januar Arif Fatkhurrahman; Farida Crisnaningtyas; Moch. Syarif Romadhon (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2018)
Dry Rubber Content (DRC) describes a rubber particle percentage in natural rubber latex. In this paper, the relation between forward light scattering profiles of natural latex and rubber contents is reported for dry rubber content latex. The profile, characterized by Full Width at Half Maximum (FWHM), is increasing linearly with respect to rubber content. The measurement was performed immediately after latex being tapped with necessary addition of acetic acid. This addition was meant to prevent latex coagulation. There is a high linear correlation between DRC and FWHM of both domain: one and two dimension. This is indicated by correlation factor which are higher than 0.9 for both of domains and sufficient in DRC determination.